The Influence of Recommendation Systems and AI Chatbots on Customer Experience on Shopee - Hendrata, Florence; Mulyawati, Cindy; Florensia, Erika (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The use of artificial intelligence technologies has become increasingly dominant in the e-commerceindustry, particularly through the implementation of recommendation systems and AI-based chatbots to enhance digital service quality. This study aims to analyze the influence of recommendation systems and AI chatbots on customer experience on the Shopee platform. The research employed a quantitative approach using a survey method involving 155 active Shopee users selected through purposive sampling. The research instrument consisted of 25 statement items that were proven to be valid and reliable. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that recommendation systems have a positive and significant influence on customer experience, while AI chatbots also have a positive and significant effect. Simultaneously, both variables contribute to shaping customer experience in the use of Shopee services. These findings confirm that artificial intelligence technologies play an important role in creating a more personalized, efficient, and satisfying customer experience. This study provides practical implications for e-commerce platforms to continuously optimize the quality of recommendation systems and AI chatbots as astrategic effort to enhance customer experience and maintain competitiveness.